If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-6)-8x+2+(2x+1)=0
We add all the numbers together, and all the variables
-8x+3(x-6)+(2x+1)+2=0
We multiply parentheses
-8x+3x+(2x+1)-18+2=0
We get rid of parentheses
-8x+3x+2x+1-18+2=0
We add all the numbers together, and all the variables
-3x-15=0
We move all terms containing x to the left, all other terms to the right
-3x=15
x=15/-3
x=-5
| -207=5(8x+3)+8x | | 6x=7+2x | | 4(3k-6)=6(3k+5 | | 6y-15=19 | | 18-6x=-7(x-2) | | 4y^2-4y=48 | | 2a-3(a-4)=-2 | | 142=1/2h(7+10 | | 0.75*10^w/3=30 | | A=1/2h(7+10) | | 6(u+3)=7 | | 5+(1+s)=-9s+6 | | 6c+2=2c+18 | | 2x-9=25-5 | | 94=4x-7 | | 2x²-3x-5=0 | | 15+20x-10=15x-5x+50 | | -2x+3=-5x-4 | | -4+h=-h−10 | | 6x=1344-42x | | 19-7k=-(6k+2) | | 36=6(w-1 | | (5+z)(4z-6)=0 | | 320÷4x=12x | | 5(7x-8)=64 | | 3x+10-x=12+x | | 6y=12.8= | | 12p+111=185 | | 4a-7+3a+8=0 | | 12p+11=285 | | 4n+(3-2n)=21 | | 8(v-7)=-4v-8 |